2019
DOI: 10.1096/fj.201902535r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at Serine 21 in G protein‐coupled receptor kinase 1 (GRK1) is required for normal kinetics of dark adaption in rod but not cone photoreceptors

Abstract: phosphodiesterase 6; PP2A, protein phosphatase 2A; pGRK1, GRK1 phosphorylated on Serine 21; RPE, retinal pigment epithelium; SEM, standard error of the mean. AbstractTimely recovery of the light response in photoreceptors requires efficient inactivation of photoactivated rhodopsin. This process is initiated by phosphorylation of its carboxyl terminus by G protein-coupled receptor kinase 1 (GRK1). Previously, we showed that GRK1 is phosphorylated in the dark at Ser21 in a cAMP-dependent manner and dephosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…These observations are consistent with our previous report showing that mice with a mutation in Grk1 that converts the phosphorylation site, Ser21, to alanine have delayed dark adaptation ( 30 ) in rods but not cones and led us to examine the phosphorylation of Grk1 in the ‘all-cone’ retina of Nrl−/− mice. Mice deficient for the Nrl transcription factor possess retinas lacking rods and instead consist mostly of modified S-cones ( 37 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These observations are consistent with our previous report showing that mice with a mutation in Grk1 that converts the phosphorylation site, Ser21, to alanine have delayed dark adaptation ( 30 ) in rods but not cones and led us to examine the phosphorylation of Grk1 in the ‘all-cone’ retina of Nrl−/− mice. Mice deficient for the Nrl transcription factor possess retinas lacking rods and instead consist mostly of modified S-cones ( 37 ).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, while PKA⍺ phosphorylated both GRK1 and GRK7 in vitro , our observations of Grk1 phosphorylation in retinas of grk1a−/− and grk1b−/− zebrafish as well as in the ‘all cone’ retina of the Nrl−/− mouse strongly suggest that Grk1 in vertebrate cones is not phosphorylated in a cAMP-dependent manner. This observation agrees with both our previous report of GRK1-S21A mice displaying a significant delay in dark adaptation in rods but not in cones ( 30 ), as well the results of this report showing that Grk7a but not Grk1b modulates recovery of the cone photoresponse in forskolin-treated zebrafish larvae.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Taken together, these findings suggest that PKA promotes the dark adaptation of rods. In support of this notion, recent studies by Kolesnikov and colleagues reported a delayed rod dark adaptation in mutant mice whose GRK1 is mutated to block its cAMP-dependent phosphorylation (65). PKA phosphorylates GRK1 to reduce its rhodopsin phosphorylation ability (19), which, in turn, extends the active lifetime of rhodopsin to increase the photosensitivity.…”
Section: Discussionmentioning
confidence: 89%
“…We previously reported that both Grk1b and Grk7a contribute to recovery of the cone photoresponse in zebrafish, which possess a retinal GRK expression pattern similar to humans, and confirm the participation of both kinases in the return of cone photoreceptors to the dark-adapted state (27). We recently reported that dark adaptation was significantly decreased in vivo in the rods of mice expressing GRK1 with the mutation Ser21Ala, which blocks phosphorylation (28). This suggests a role for cAMP-dependent phosphorylation of GRK1 in modulating the lifetime of activated rhodopsin.…”
Section: Introductionmentioning
confidence: 99%